REVITALISASI KAWASAN PARIWISATA BERBASIS BUDAYA UNTUK MENINGKATKAN EKSISTENSI BUDAYA LOKAL DI KABUPATEN BULELENG - Widyani Nyoman (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2017)
Research on the revitalization of local culture-based tourism area aims to describe: (1) cultural values  that can be used in tourism sector in Buleleng,  (2) revitalization strategy of local culture-based tourism area that can be used to improve the existence of local culture in Buleleng. This research is a qualitative descriptive research.  Informants in this research are cultural and community who work in the cultural and tourism sector. Data were collected by interview. Data analysis was done by descriptive method. The result of revitalization research of local culture-based tourism area shows that: local cultural values (Buleleng) that can be used in tourism sector are cultural values based on Tri Hita Karana philosophy. Implementation of the concept of parahyangan can be done by building places of worship around the tourist area, conducting praying activities. Implementation of the concept of pawongan can be done by greeting each  other with  "Om  Swastyastu" to  all  people  encountered  and  maintain intimacy  among religious  people.  Implementation  of the  concept  of  palemahan  can  be  done  by  not littering, keeping the  environment free  of  air  pollution,  greening  and tree  planting,  maintaining  the environment. Strategy of revitalization of local culture-based tourism area that can be used to improve the existence of local culture in done through four things, namely: (1) tourist attractions, (2) tourist attractions, (3) tourism promotion, (4) tourism partnership. Associated with tourist attractions, revitalization efforts made more on efforts to improve tourist sites. Related attractions revitalization efforts undertaken in the form of improvement of every activity / activity of art and local culture. Related promotion tour. Done by offering cultural tour packages. Related to tourism partnerships can be built cooperation to introduce the culture of Buleleng Regency. Keywords: Culture, Tourism, Revitalization